Treatment of skin diseases - Pasricha, J.S (Jaypee, 2013)
This sixth edition brings medical trainees and practising dermatologists fully up to date with the latest developments and advances in the treatment of skin diseases. It provides a comprehensive approach to the recognition, diagnosis and treatment of various dermatological conditions. Each chapter has been thoroughly revised to include new techniques for diagnosis and treatment, as well as up to date information on existing methods. The book includes new photographs and a completely revised appendix detailing common drugs, their dosage and possible side effects.